An overview of platelet function in normal and complicated pregnancies. (July 2013) - Burke, Naomi; Flood, Karen; Muellers, Sieglinde; Murray, Aoife; Dempsey, Mark; Geary, Michael; Kenny, Dermot; Malone, Fergal
<x xml:space="preserve">Abstract</x> The pregnant state must achieve a fine balance between hemorrhage and thrombosis. Platelets play a critical role in this balance yet there is a lack of clear knowledge and consensus about platelet function in pregnancy. This review will outline the mechanisms involved in platelet clot and thrombus formation, delineate the different techniques available for the assessment of platelet function and highlight the current understanding of platelet function in pregnancy. With respect to normal pregnancy, there appears to be an increase in platelet aggregation when compared with the nonpregnant state. In pregnancies complicated by pre-eclampsia and intrauterine growth restriction, platelets are further activated when compared with normal pregnancy. Platelet function testing in those with recurrent miscarriage suggests a tendency toward thrombosis. However, further studies are needed to clarify platelet function status in normal and complicated pregnancy.